Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
x = -6
y = 2
Step-by-step explanation:
1. Approach
x - 3y = -12
4x + 6y = -12
In this problem, it would likely be easier to use elimination, but since the problem specifically says that one must use substitution, substitution will be used. Substitution is when one solves one of the equations for a variable, similar to solving a literal equation. The one will substitute in the value of the variable into the other equation and solve for the other varibale. Then one will finally back substitute in that value of the other variable to find the value of the first variable, hence solving the equation.
2. Solve equation 1
x - 3y = -12
Solve the literal equation with inverse operations;
x - 3y = -12
+3y + 3y
x = 3y - 12
3. Substitute the answer into the second equation
4x + 6y = -12
x = 3y - 12
4 ( 3y - 12 ) + 6y = -12
Distribute;
12y - 48 + 6y = -12
Simplify;
12y - 48 + 6y = -12
18y - 48 = -12
Inverse operations;
18y - 48 = -12
+48 +48
18y = 36
/18 /18
y = 2
4. Backsolve for x
Substitute the value for y back into the equation for x and solve
x = 3y - 12
y = 2
x = 3(2) - 12
x = 6 - 12
x = -6
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.